Hybrid fiber-reinforced biocomposites for marine applications: a review - Huang, Yang; Sultan, Mohamed Thariq Hameed; Shahar, Farah Syazwani; Grzejda, Rafał; Łukaszewicz, Andrzej (Multidisciplinary Digital Publishing Institute, 2024)
Highly efficient fiber-reinforced composites find extensive application in diverse industries. Yet, conventional fiber-reinforced composites have significant environmental impacts during both manufacturing and disposal. Environmentally friendly fiber-reinforced composites have garnered significant attention within the framework of sustainable development. Utilizing natural fibers in place of synthetic fibers and progressively decreasing the use of synthetic fibers are the main approaches to achieving a balance between economic progress and environmental quality. Attention is increasingly being drawn to natural fiber-reinforced biocomposites that exhibit outstanding environmental performance, exceptional physical and mechanical capabilities, and biological features. The lightweight and high-strength characteristics of these biocomposites enable them to significantly decrease the weight of structures, making them increasingly popular in many industries. The objective of this review is to evaluate the effectiveness of hybrid fiber-reinforced biocomposites in marine applications, specifically examining their mechanical characteristics, resistance to seawater, and ability to absorb moisture, all while advocating for sustainable material methodologies. To achieve this objective, the paper delineates the distinction between synthetic and natural fibers, examines the benefits of hybrid fiber-reinforced biocomposite materials, and addresses the obstacles and effective approaches in their production and application in seawater. Considering the review analysis, it can be inferred that the use of fiber-reinforced biocomposites in maritime applications shows significant potential and has abundant untapped growth prospects in the future years.